Fibrosis markers and CRIM1 increase in chronic heart failure of increasing severity. (May 2014) - Eleuteri, Ermanno; Di Stefano, Antonino; Vallese, Davide; Gnemmi, Isabella; Pitruzzella, Alessandro; Tarro Genta, Franco; Delle Donne, Lorena; Cappello, Francesco; Ricciardolo, Fabio L. M.; Giannuzzi, Pantaleo
Abstract Background: Fibrosis suppressors/activators in chronic heart failure (CHF) is a topic of investigation. Aim: To quantify serum levels of fibrosis regulators in CHF. Methods: ELISA tests were used to quantify fibrosis regulators, procollagen type-(PIP)I, (PIP)III, collagen-I, III, BMP1, 2, 3, 7, SDF1α, CXCR4, fibulin 1, 2, 3, BMPER, CRIM1 and BAMBI in 66 CHF (NYHA class I, n = 9; II, n = 34; III n = 23), and in 14 controls. Results: In CHF, TGFβR2, PIPIII, SDF1α and CRIM1 were increased. PIPIII correlated with CRIM1. Conclusions: The BMPs inhibitor CRIM1 is increased and correlates with higher levels of serum PIPIII showing an imbalance in favor of pro-fibrotic mechanisms in CHF.